Model Peramalan Inflow Waduk Plta Koto Panjang Menggunakan Pendekatan Adaptive Neuro Fuzzy Inference System - Handayani, Yohanna Lilis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Many studies has shown that the ANFIS  model  has good prediction performance results for forecasting hydrological phenomena such as reservoir inflow. The existence of the success, it is necessary to research the  reliability of the ANFIS models when applied to existing reservoirs in  Riau Province, namely  Koto Panjang Hydropower Reservoir. The results of  the ANFIS  models  in the  development  phase  of this  study indicate that the scheme 4 (4 inputs) with the ROI value of 0.02 is the best scheme so that the scheme is used to build the model of ANFIS. The cross validation on ANFIS models  provide  the best  performance  prediction  with  correlation coefficient (R) between the prediction values and the observational value is 0.90. Keywords:  Inflow, Koto Panjang Hydropower Reservoir, ANFIS, Cross Validation .